Implementation of the Non-Discrimination for Employees Principle under Manpower Law - Ongnot Hersiani; Ariani Yestati; Elin Sudiarti; Syamhudian Noor (Jurnal Daulat Hukum, 2026)
This study examines the implementation of the principle of non-discrimination under Law Number 13 of 2003 on Manpower at PT. Trio Motor in Kuala Kurun, Gunung Mas Regency. The research is motivated by the existence of company policies prohibiting married couples from working in the same unit and the dismissal of female employees after marriage, which potentially contradict the principle of equal treatment in employment relations. The purpose of this study is to analyze the implementation of the principle of non-discrimination in company practices and to assess its conformity with Indonesian labor law and ILO Convention Number 111 of 1958. This research employs an empirical juridical method by combining statutory analysis with field research through interviews, observations, and literature studies. The data obtained are analyzed using a descriptive qualitative approach to evaluate the implementation of Articles 5, 6, and 153 paragraph (1) of Law Number 13 of 2003 on Manpower. The findings show that the implementation of the non-discrimination principle at PT. Trio Motor is still not optimal, as company policies prioritize professionalism and conflict prevention over equal treatment for workers. Consequently, a gap remains between normative legal provisions and employment practices.